2020
DOI: 10.1002/ehf2.13119
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of echocardiographic quantification of left ventricular filling pressure

Abstract: Aims The clinical reliability of echocardiographic surrogate markers of left ventricular filling pressures (LVFPs) across different cardiovascular pathologies remains unanswered. The main objective was to evaluate the evidence of how effectively different echocardiographic indices estimate true LVFP. Methods and results Design: this is a systematic review and meta‐analysis. Data source: Scopus, PubMed and Embase. Eligibility criteria for selecting studies were those that used echocardiography to predict or est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…E/E′ has been the main non-invasive surrogate parameter to predict LVFP. However, many studies demonstrated that E/E′ ratio has a weak correlation with pulmonary capillary wedge pressure (PCWP) in patients with HFpEF [ 43 48 ]. Overall, there is a lack of strong evidence in HFpEF patients supporting the utility of E/E′ as an accurate marker of LVFP.…”
Section: Discussionmentioning
confidence: 99%
“…E/E′ has been the main non-invasive surrogate parameter to predict LVFP. However, many studies demonstrated that E/E′ ratio has a weak correlation with pulmonary capillary wedge pressure (PCWP) in patients with HFpEF [ 43 48 ]. Overall, there is a lack of strong evidence in HFpEF patients supporting the utility of E/E′ as an accurate marker of LVFP.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, significant controversy exists within the literature regarding the use of the mitral E/e′ alone as a marker of diastolic dysfunction and elevated left ventricular filling pressures. 36 , 37 There are numerous clinical variables that can degrade the association between the E/e′ ratio and the left ventricular filling pressures, and we could neither identify the presence of these factors in our cohort nor could we confirm the presence of elevated left ventricular filling pressures via invasive haemodynamics assessment. 29 We did not have adequate data to formally grade diastolic dysfunction in this cohort according to current guidelines, which might have greater accuracy for elevated left ventricular filling pressures.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, these echocardiographic data are merely a snapshot at a single time point in a patient's course, and fail to capture the inherent variability and changing nature of haemodynamics, particularly after ACS. Finally, significant controversy exists within the literature regarding the use of the mitral E/e′ alone as a marker of diastolic dysfunction and elevated left ventricular filling pressures 36,37 . There are numerous clinical variables that can degrade the association between the E/e′ ratio and the left ventricular filling pressures, and we could neither identify the presence of these factors in our cohort nor could we confirm the presence of elevated left ventricular filling pressures via invasive haemodynamics assessment 29 .…”
Section: Discussionmentioning
confidence: 83%
“…However, even within a niche field like HF, it is possible to analyse which issues gain more interest and are more requested, thus partially representing the ‘news value’ of a journal. Tables 2–5 report the top 10 articles published in 2019 and 2020 in the European Journal of Heart Failure and ESC Heart Failure , according to their Altmetric Attention Score 5–44 . 2020 was the year of…”
Section: Communication Means Pointsmentioning
confidence: 99%